Comparison of X-ray diffraction measurement of residual elastic strains: monochromatic beam and image plate versus white beam energy-dispersive analysis - Vorster, W; Zhang, S; Golshan, M; Laundy, D; Dini, D; Korsunsky, A (Professional Engineering Publishing, 2007)
This paper presents the results of synchrotron X-ray diffraction measurement of residual elastic strains in a bent magnesium alloy bar using two different techniques. In the first technique the sample was scanned transversely to a monochromatic X-ray beam. The scattered X-rays were recorded on a phosphoric image plate that was translated at a proportional speed but in the opposite direction to the sample. This enabled the creation of a two-dimensional recording of one-dimensional diffraction patterns. In the second technique a white X-ray beam is used in combination with an energy-discriminating detector mounted at a fixed angle to record similar patterns at each gauge volume position within the sample. The motivation for comparing the results of two measurement techniques is to establish whether the same accuracy in a diffraction strain evaluation can be achieved. It was found that the translating image plate arrangement requires a certain amount of care in calibration and interpretation, but provides a quick and efficient method that can be competitive with the white beam energy-dispersive mode which is known to deliver a fast diffraction capability.